Activities of the 23rd Frontier Squad of Intelligencerson Blocking the Coastal Zone in Lithuania in 1954–1958 - Starkauskas, Juozas (Genocidas ir rezistencija, 2002)
With reference to a moderate fond of thirty files stored in the Special Archives of Lithuania, the article describes activities of the 2nd intelligence division of the SSRS KGB frontier troops’ 23rd frontier squad, in part and of the entire squad. Since February 1945 up until the collapse of the Soviet Union this squad blocked the coast of Lithuania and the Kaliningrad region (former Eastern Prussians) (for some time also a part of the Latvian coast), and a small range of the land board between Kaliningrad region and Poland, all in all about 250 km. Activities of the frontier squads got complicated due to the ports where more foreign ships would come each time, as well as due to numerous visitors in the sea resorts, the most famous of which was Palanga. One more issue of concern was Klaipėda land which had been occupied by the Hitler’s Germany just before the war in 1939 and where a part of citizens were of German origin, but did not manage to move westwards during the war. This part of citizenry considered themselves as Lithuanians and was positive that they would not manage to get along with the Soviet regime, so they put many efforts to leave westwards or at least to the eastern Germany. Hundreds of them corresponded with their relatives living abroad. In 1955, hundreds of former political prisoners and deportees started returning home. All they became the objects of supervision by the KGB structures, frontier intelligences, and were considered to be potential state enemies. Mostly supervised were those who had one or another way expressed their will to flee the Soviet Union (the number of such people at the frontier ranged from 20 to 50 at different time).